A Digital Platform to Support the Design and Creation of Digital Social Innovations - Kornelia BATKO; Kamila BARTUŚ (Communications of International Proceedings, 2021)
This article presents definitions of social innovation and digital social innovation and describes the stages of the process of creating digital social innovation. The purpose of this article is to present the author's model of an online platform for supporting the creation and development of social innovations. The concept of this solution was developed on the basis of literature review, case study and authors' own experience. The proposed system, the platform for supporting social innovation is to support the authors in subsequent stages of creating and developing digital social innovations.
Keywords: Social Innovation; Digital Social Innovation; Computer Assisted Digital Social Innovation; Digital Platform Assisted Social Innovation.